Prática de ensino de química e metodologia investigativa: uma leitura fenomenológica a partir da semiótica social - Zuliani, Silvia Regina Quijadas Aro (2006)
The Practical of Education, as integrating disciplines between the specific knowledge of Sciences and the pedagogical knowledge for the teaching exercise have become the locus of the quarrel about educational formation. In this work we present the results of a research carried through a project of intervention, made with Chemistry studensts, based in the Investigative Methodology, in the development of the discipline Practical of Chemical Education I and II, at the Universidade Federal de São Carlos. The objective of this research was to search the perceptions of the students about their own learning and its transference to other contexts, useing the referencial considered by the Fenomenology and by Social Semiotic for data analysis. This analysis confirms the potential of the methodology proposal in the metacognitive development of the students and indicates a process in their conceptions. Gradually they perceive the construction of learning strategies as a process of personal construction. On the other hand, a valuation of this construction occurs as professional knowledge that needs to be developed in the pupils through the performance of the teacher (transference to other contexts and applicability of the knowledge). The reflection propitiated for the students took them to recognize the complementarity between teaching and learning, becoming both unassociable.The pupils were capable to construct and to reconstruct the meaning of learn with the final point in the perception of the responsibility for the own process of learning and in the necessity of applying these knowledge in new contexts, including the professional activity.